Clinical and care profile of two ICUs in a University Hospital through the analysis of indicators of a physiotherapy service (Research, Society and Development, 2021)
Objective: To analyze critically and comparatively, through indicators, the clinical and care profile of patients admitted to the General Intensive Care Units and COVID of a University Hospital in Sergipe. Methods: Epidemiological, observational and longitudinal study, developed in the year 2020. Clinical and care data were collected daily, during the established hospitalization period, from which the quality indicators were composed. A statistical analysis was performed using Student's t and Chi-square tests, considering a level of significance, p